Can Civil Society Overcome Government Failure in Africa? - Devarajan, Shantayanan (Oxford University Press on behalf of the World Bank, 2015)
Government failures are widespread in Africa. Symptoms include absentee teachers, leakage of public funds, monopolized trucking, and employment-restricting regulations. Can civil society do anything about these failures? Would external donor support to civil society help? We argue that the challenge for civil society is to improve government functioning by strengthening political incentives—the underlying cause of government failure—rather than bypassing or supplanting the state. This paper reviews the available evidence on civil society interventions from this perspective. Although the current increase in political competition and extensive citizen engagement in Africa seems to create the potential for civil society influence, we find that there are large knowledge gaps regarding what works, where, and how. Some rigorous evaluations find significant impacts of civil society involvement on development outcomes, but these studies typically pay insufficient attention to the mechanisms. For example, are impacts due to overcoming government failure or to changing private household behavior, leaving the wasteful allocation of public resources untouched? We conclude that donor support to civil society should take an approach of learning by doing through ongoing experimentation backed by rigorous, data-based evaluations of the mechanisms of impact.